Исследование характеристик ЧМН-2 сигналов, формируемых с помощью синтезатора частот косвенного типа - Сыроветник, В. С. (ХНУРЭ, 2009)
The given report is devoted to research of characteristics of the BFSK signals formed by FS indirect type. In particular, spectral characteristics of the BFSK signals are determined at various modes of frequency transient. Besides, noise stability parameters are determined at various reception methods.
Keywords: ЧМН-2 сигнал; синтезатор частот косвенного типа; сети связи